2018
DOI: 10.1002/jclp.22729
|View full text |Cite
|
Sign up to set email alerts
|

Physician referral to a psychologist: Testing alternative behavioral healthcare seeking models

Abstract: Objective: Primary care physicians (PCPs) often refer patients to psychological services, but help-seeking factors in the context of behavioral healthcare referral are understudied. This study examined perceptions of seeking psychological help for depression by comparing alternative structural equation models derived from the Theory of Reasoned Action (TRA). Method: Internet survey participants (N = 685 US adults, 77% female, M age = 45) imagined themselves in a vignette scenario in which they are experiencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In their research, extrinsic rewards were found to have a salient impact on intention to share medical expertise through attitude. Hammer et al. (2019) also employed the TRA in their research to investigate the determinants influencing patients' intention to seek mental health assistance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In their research, extrinsic rewards were found to have a salient impact on intention to share medical expertise through attitude. Hammer et al. (2019) also employed the TRA in their research to investigate the determinants influencing patients' intention to seek mental health assistance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Kravitz et al (2006) found some support for physicians making mental health referrals, but physicians' offices were not found to be likely to offer significant assistance in helping individuals follow-through on mental health referrals. Hammer, Spiker, and Perrin (2018) discussed how most patients will initially seek mental health assistance through their primary care provider, but only about one third will follow through on a referral to a mental health provider.…”
Section: Introductionmentioning
confidence: 99%